Chemical, Manufacturing, and Standardization Controls of Grape Polyphenol Dietary Supplements in Support of a Clinical Study: Mass Uniformity, Polyphenol Dosage, and Profiles - Lyu, Weiting; Rodriguez, David; Ferruzzi, Mario G.; Pasinetti, Giulio M.; Murrough, James W.; Simon, James E.; Wu, Qingli (Frontiers in Nutrition, 2021)
Bioactive dietary polyphenols in grape (Vitis vinifera) have been used in Dietary Supplements (DSs) with the aim to prevent numerous diseases, including cardiovascular and neurodegenerative diseases, and to reduce depression and anxiety. Given prior recognition that DSs can be quality challenged from the purity, authentication, adulteration, and actual concentration of targeted bioactives, to ensure consumer health protection as well as the quality and safety of grape polyphenol-based DSs, the present investigation was aimed at establishing a comprehensive quality control (QC) approach for grape polyphenol-based DSs in support of a human clinical study. In this study, the manufactured grape seed polyphenol extract (GSPE) and trans-resveratrol (RSV) capsules and Concord Grape Juice (CGJ) along with the corresponding original drug materials were analyzed using the developed different liquid chromatography/UV-visible spectroscopy/mass spectrometry (LC/UV-Vis/MS) methods. The weight variation of GSPE and RSV capsules was also evaluated according to the US Pharmacopeia (USP) tests. The results indicate that the total identified polyphenol content in each grape seed extract (GSE) capsule/CGJ is very similar and all GSE/RSV capsules pass the content/weight uniformity test. Given the complexity of these and many botanical products from the issues of purity, quality, adulteration, consistency, and their coupling to the complex chemistry in each grape-derived botanical, quality assurance and the steps needed to ensure grape-derived DSs being well homogeneous and stable and containing the known and expected bioactives at specific concentration ranges are fundamental to any research study and in particular to a clinical trial. Each of these issues is essential to provide a solid foundation upon which clinical trials with botanicals can be conducted with the goal of realizing measurable mental health outcomes such as reducing depression and anxiety as well as understanding of their underlying biological mechanisms.